Relationship between carotid intima-media thickness and white matter hyperintensities in non-stroke adults: a systematic review - Humayra, Syeda; Yahya, Noorazrul; Ning, Chai Jia; Raffali, Mohd Asyiq Al-Fard bin Mohd; Mir, Imtiyaz Ali; Mohamed, Abdul Latiff; Manan, Hanani Abdul (Frontiers in Neuroanatomy, 2024)
Introduction Literature suggests a common pathophysiological ground between carotid atherosclerosis (CAS) and white matter alterations in the brain. However, the association between carotid intima-media thickness (CIMT) and white matter hyperintensities (WMH) has not been conclusively reported. The current systematic review explores and reports the relationship between CIMT and WMH among asymptomatic/non-stroke adults. Methods A recent literature search on PubMed, SCOPUS, and Web of Science databases was conducted in compliance with the PRISMA protocol. The pre-defined Population-Intervention-Comparison-Outcome-Study (PICOS) criteria included observational studies investigating the CIMT-WMH association among non-stroke adults undergoing magnetic resonance imaging and carotid ultrasound. Results Out of 255 potential results, 32 studies were critically assessed for selection, and finally, 10 articles were included, comprising 5,116 patients (females = 60.2%; males = 39.8%) aged between 36–71 years. The included studies earned high quality ratings (6–9) based on the Newcastle-Ottawa-Scale criteria. Qualitative synthesis showed a significantly parallel relationship between increased CIMT and greater WMH burden in 50% of the studies. In addition, significant risk factors related to the CIMT-WMH association included older age, hypertension, depression, migraine, Hispanic ethnicity, and apolipoprotein E (ɛ4) in postmenopausal women. Conclusion Overall, the cumulative evidence showed a consistent CIMT-WMH association in asymptomatic middle-aged and older non-stroke adults, indicating that CAS may contribute to the progression of pathologically hyperintense white matter in the brain. However, further research is warranted to infer the plausible relationship between CIMT and WMH in the absence of stroke.